RELIGIOSITY AMONG AUTISTIC CHILDREN: The Formation of Religious Practices and Islamic Spiritual Experiences - Ampun Bantali; Sjafri Sairin; Fuad Nashori; Azam Syukur Rahmatullah (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2026)
Children with Autism Spectrum Disorder (ASD), despite their developmental limitations, remain spiritual subjects who can be introduced to religious life. This study investigates the nature of autistic children’s spiritual experiences, the significance of nurturing religiosity, and the strategies used to cultivate religious practices. Employing a phenomenological design, the research was conducted in North Sumatra with six informants: three autistic children and their parents. Data were collected through in-depth interviews. The findings reveal diverse patterns of religiosity: some children display difficulties grasping the abstract concept of God, while others develop heteronomous faith shaped largely by parental instruction and environmental exposure. Religious practices are typically performed through routine imitation rather than internalized theological comprehension. However, sustained parental guidance and supportive environments appear to foster more complex forms of religiosity. Importantly, religiosity functions not only as spiritual formation but also as a psychosocial resource that promotes self-regulation, emotional stability, and reduced anxiety. Effective strategies include habituation, modeling, repetition, and active engagement within supportive and inclusive communities.